Pengaruh Interaksi Edukatif Dan Pemberian Reward Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI IPS SMA Negeri 1 Uluan Tahun Ajaran 2022/2023 - Meiriza, Mica Siar; Samosir, Endang (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of educational interactions and the provision of rewards on student learning achievement in the economics subject class XI IPS SMA Negeri 1 Uluan for the academic year 2022/2023. There are 65 students as a population and sample with a total sampling technique. In addition, data was collected by using documentation and a questionnaire. The results of the research that can be seen from the acquisition of statistical data prove that there is a positive and significant influence between the variables of educational interactions and the provision of rewards on student achievement. The equation that can be obtained is Y = Y = 28.269 + 0.3888X1 + 0.292X2. The data obtained on the coefficient of determination test (R Square) is 0.522. That is, educational interactions and the provision of rewards simultaneously on student achievement are 52.2%, and the remaining 47.8% are influenced by other factors not examined in this study.